2023
DOI: 10.1039/d3cb00150d
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic labelling of DNA in cells by means of the “photoclick” reaction triggered by visible light

Lisa Rieger,
Bastian Pfeuffer,
Hans-Achim Wagenknecht

Abstract: Two pyrene-tetrazole conjugates were synthesized as photoreactive chromophores that allow for the first time the combination of metabolic labelling of DNA in cells and subsequent bioorthogonal “photoclick” modification triggered by visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The subsequent photoclick labeling was attempted with the pyrene‐tetrazole conjugate 13 . This dye can be photoactivated by visible light (405/450 nm LEDs), and the subsequent reaction of the nitrilimine is fluorogenic [3c] . The postsynthetic DNA labeling attempts, however, were not successful, neither with tetrazole 13 nor with 9 , likely due to the insolubility of the oligonucleotide samples in MeCN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent photoclick labeling was attempted with the pyrene‐tetrazole conjugate 13 . This dye can be photoactivated by visible light (405/450 nm LEDs), and the subsequent reaction of the nitrilimine is fluorogenic [3c] . The postsynthetic DNA labeling attempts, however, were not successful, neither with tetrazole 13 nor with 9 , likely due to the insolubility of the oligonucleotide samples in MeCN.…”
Section: Resultsmentioning
confidence: 99%
“…The postsynthetic DNA labeling attempts, however, were not successful, neither with tetrazole 13 nor with 9 , likely due to the insolubility of the oligonucleotide samples in MeCN. We know from our photoclick experiments in vitro and in cells that this chemistry requires substantial amounts of organic solvent, the most suitable is MeCN [3c] . Although this is an experiment with a negative outcome, it is an important result because it helped us to adjust the protocol for the dual metabolic labeling in a cellular environment, as described below.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the Wagenknecht group came up with new strategy by combining VdU with tetrazoles involved "photoclick" reaction [14] to enable the labeling with spatiotemporal resolution. [15] Zhang et al demonstrated efficient and fluorogenic live cell labeling of DNA using a watersoluble tetrazole, activated by irradiation with 350 nm light. By utilizing VdU as a building block as well.…”
Section: Metabolic Labeling Of Dnamentioning
confidence: 99%
“…This strategy enables the live‐cell dynamic imaging of nucleic acids and provides a mix‐and‐measure fluorogenic assay for DNA replication. More recently, the Wagenknecht group came up with new strategy by combining VdU with tetrazoles involved “photoclick” reaction [14] to enable the labeling with spatiotemporal resolution [15] . Zhang et al.…”
Section: Cellular Metabolic Labeling Of Nucleic Acidsmentioning
confidence: 99%
“…A most recent example was presented by Rieger et al, who metabolically incorporated 5vinyl-2'-deoxyuridine (VdU) into HeLa cells. [36] After fixation and denaturation, photoirradiation with a 450 nm LED in the presence of a pyrene-substituted tetrazole allowed the visualization of the genomic DNA. Further, upon conversion of the tetrazole moiety in the photoclick reaction, a change in the fluorescence color and fluorogenicity could be observed.…”
Section: Metabolic Labeling Of Nucleic Acidsmentioning
confidence: 99%